Phylogeny of the genus Syncirsodes (Lepidoptera: Geometridae) - Sepúlveda-Zúñiga, Einer; Parra, Luis E.; Zamora-Manzur, Carlos; Bocaz-Torres, Patricia (Revista Colombiana de Entomología, 2016)
In this study, the phylogeny of species in the genus Syncirsodes Butler, based on morphological characters, was determined. Species included were: S. distictaria, S. hyadesi, S. primata, and S. straminea. Twenty-seven morphological characters of adult external and internal structures were used, with principal emphasis on male and female genitalia and metafurcasternum. A parsimonious cladogram (L = 51, CI = 0.94, RI = 0.83) was made. The phylogenetic hypothesis suggests two groups of sister species: S. distictaria + S. straminea and S. hyadesi + S. primata.